Effects of static and progressively increasing prey density regimens on larval performance of largemouth bass (Micropterus nigricans) reared in an intensive recirculating aquaculture system - Nelson S. Parajuli; Robert Glennon; Anneleen Swanepoel; Dustin Goodman; Josh Sakmar; Allen Nicholls; Luke A. Roy; D. Allen Davis; Timothy J. Bruce; Ian A.E. Butts (Aquaculture, 2027)

Impact of light intensity and tank color on growth and development of largemouth bass, Micropterus nigricans, during early life history - Anneleen Swanepoel; Nelson S. Parajuli; Kaylan Martin; Kyle R. Wood; Josh Sakmar; Allen Nicholls; Anita M. Kelly; Luke A. Roy; Timothy J. Bruce; D. Allen Davis; Ian A.E. Butts (Aquaculture, 2026)

Predator and prey density effects on early life-history performance of largemouth bass (Micropterus nigricans) in an indoor recirculating aquaculture system - Nelson S. Parajuli; Josh Sakmar; Allen Nicholls; Anita M. Kelly; Luke A. Roy; D. Allen Davis; Timothy J. Bruce; Matthew K. Litvak; Ian A.E. Butts (Aquaculture, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Overview of BLOOFINZ/INDITUN investigations of the southern bluefin spawning region off northwest Australia, January–March 2022 - Michael R. Landry; Raúl Laiz-Carrión; Sven A. Kranz; Karen E. Selph; Michael R. Stukel; Estrella Malca; David Die; Lynnath E. Beckley; Moira Décima; Rasmus Swalethorp; José M. Quintanilla; Natalia Yingling; et al. (Deep Sea Research Part II: Topical Studies in Oceanography, 2025)

“The use of Corn fermented protein as a protein source complement with soybean meal in practical diets in pond and tank based production of Pacific white shrimp (Litopenaeus vannamei).” - Cristhian F. San Andres; Khanh Q. Nguyen; Jairo A. Gonzalez; Arnold J. Gutierrez; Melanie A. Rhodes; Julio García; Luke A. Roy; D. Allen Davis (Animal Feed Science and Technology, 2025)

Influence of dietary fermented yeast products (Saccharomyces cerevisiae) on performance, health and microbiome of Nile tilapia (Oreochromis niloticus) and the influence of discharge water in the production of romaine lettuce (Lactuca sativa) - Uthpala M. Padeniya; D. Allen Davis; Daniel E. Wells; Courtney E. Harrison; Benjamin R. LaFrentz; Benjamin H. Beck; Luke A. Roy; Mark Farmer; Timothy J. Bruce (Animal Feed Science and Technology, 2025)

Anthozoan eDNA primer set characterizes Ctenophora and Medusozoa inhabiting mesophotic and deep waters off the Gulf Coast of the southern USA - Annemarie Wood; Luke McCartin; Santiago Herrera; Andrea M. Quattrini; Allen G. Collins (Frontiers in Marine Science, 2025)
While gelatinous zooplankton (GZ) constitute a vital component of the marine food web, understanding their biology and ecology has been hindered because traditional collection methods often destroy their fragile bodies. Environmental DNA (eDNA) sequencing is a non-invasive approach that can detect organisms that are difficult to sample, enabling the DNA of understudied taxa to be sequenced. Here, we present the first application of eDNA metabarcoding targeting Ctenophora and Medusozoa. We first assessed the applicability of an anthozoan eDNA primer set designed to a 28S barcode in anthozoans for amplifying this region in ctenophores and medusozoans, including the creation of a 28S reference library for Ctenophora. After determining that the primers complement these groups well, the primers were used to analyze eDNA samples from mesophotic and deep-sea sites off the Gulf Coast of the southern USA. We recovered sequences belonging to a diverse array of GZ taxa and used these data to distinguish GZ communities by site and ecosystem type, characterize community diversity, and facilitate a better understanding of how these mysterious organisms interact within their ecosystem. The versatility of this primer set presents an exciting opportunity to research taxa that have been historically difficult to study, while further contributing to our understanding of their ecological roles in the deep sea.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Isotopically resolved fate and processes of nitrogen in a constructed wetland treating domestic effluent - Danielle J. Allen; Mark Farrell; Wei Wen Wong; Jianyin Huang; Luke M. Mosley (Science of The Total Environment, 2025)

Using seasonal palaeo-flow reconstructions and artificial neural networks for daily water balance modelling: A case study from Tasmania, Australia - Danielle C. Verdon-Kidd; Kathryn J. Allen; Luke J. Kidd; Carolyn Maxwell; Mark Willis; Patrick Baker (Global and Planetary Change, 2025)

Effects of minimum dissolved oxygen setpoints for aeration in semi-intensive pond production of Pacific white shrimp (Litopenaeus vannamei) - Adela N. Araujo; Christian F. San Andres; Khanh Q. Nguyen; Trenton L. Corby; Melanie A. Rhodes; Julio García; Luke A. Roy; D. Allen Davis (Aquaculture, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Integrated organismal responses induced by projected levels of CO 2 and temperature exposures in the early life stages of lake sturgeon - Luke D. Belding; Matt J. Thorstensen; Alex R. Quijada‐Rodriguez; William S. Bugg; Gwangseok R. Yoon; Alison R. Loeppky; Garrett J. P. Allen; Alexandra N. Schoen; Madison L. Earhart; Catherine Brandt; Jennifer L. Ali; Dirk Weihrauch; et al. (Molecular Ecology, 2024)
Atmospheric CO 2 and temperature are rising concurrently, and may have profound impacts on the transcriptional, physiological and behavioural responses of aquatic organisms. Further, spring snowmelt may cause transient increases of p CO 2 in many freshwater systems. We examined the behavioural, physiological and transcriptomic responses of an ancient fish, the lake sturgeon ( Acipenser fulvescens ) to projected levels of warming and p CO 2 during its most vulnerable period of life, the first year. Specifically, larval fish were raised in either low (16°C) or high (22°C) temperature, and/or low (1000 μatm) or high (2500 μatm) p CO 2 in a crossed experimental design over approximately 8 months. Following overwintering, lake sturgeon were exposed to a transient increase in p CO 2 of 10,000 μatm, simulating a spring melt based on data in freshwater systems. Transcriptional analyses revealed potential connections to otolith formation and reduced growth in fish exposed to high p CO 2 and temperature in combination. Network analyses of differential gene expression revealed different biological processes among the different treatments on the edges of transcriptional networks. Na + /K + ‐ATPase activity increased in fish not exposed to elevated p CO 2 during development, and mRNA abundance of the β subunit was most strongly predictive of enzyme activity. Behavioural assays revealed a decrease in total activity following an acute CO 2 exposure. These results demonstrate compensatory and compounding mechanisms of p CO 2 and warming dependent on developmental conditions in lake sturgeon. Conserved elements of the cellular stress response across all organisms provide key information for how other freshwater organisms may respond to future climate change.

Analysing spatiotemporal patterns of snake occurrence in an Australian city to help manage human-wildlife conflict - Brenton von Takach; Damian Christopher Lettoof; Tom Parkin; Alana de Laive; Luke Allen; Chris J. Jolly (Biodiversity and Conservation, 2024)

Novel insight into ammonium, phosphate, and iron(II) dynamics in the sediment porewater of a constructed wetland under artificial aeration through the diffusive equilibrium in thin films technique - Danielle J. Allen; Jianyin Huang; Mark Farrell; Luke M. Mosley (Environmental Research, 2023)

On demand feeding and the response of Pacific white shrimp (Litopenaeus vannamei) to varying dietary protein levels in semi-intensive pond production - Leila M. Strebel; Khanh Nguyen; Adela Araujo; Trenton Corby; Melanie Rhodes; Benjamin H. Beck; Luke A. Roy; D. Allen Davis (Aquaculture, 2023)

Effects of temperature and subspecies during critical early life history stages of largemouth bass (Micropterus salmoides) - Gavin L. Aguilar; Josh Sakmar; Allen Nicholls; Matthew K. Litvak; Hana N. Hess; Timothy J. Bruce; Helen R. Montague; Anita M. Kelly; Luke A. Roy; Moisés A. Bernal; Sebastian N. Politis; Ian A.E. Butts (Aquaculture, 2023)

Island Tiger Snakes (Notechis scutatus) Gain a ‘Head Start’ in Life: How Both Phenotypic Plasticity and Evolution Underlie Skull Shape Differences - Ammresh; Emma Sherratt; Vicki A. Thomson; Michael S. Y. Lee; Nathan Dunstan; Luke Allen; Jeff Abraham; Alessandro Palci (Evolutionary Biology, 2023)

Evaluation of aqueous magnesium concentration on performance of Pacific white shrimp (Litopenaeus vannamei) cultured in low salinity water of West Alabama, USA - David P. Hernández; Hisham A. Abdelrahman; Harsha S.C. Galkanda-Arachchige; Anita M. Kelly; Ian A.E. Butts; D. Allen Davis; Benjamin H. Beck; Luke A. Roy (Aquaculture, 2023)

Artificial aeration of an overloaded constructed wetland improves hypoxia but does not ameliorate high nitrogen loads - Danielle J. Allen; Mark Farrell; Jianyin Huang; Simon Plush; Luke M. Mosley (Journal of Environmental Management, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Using spatial characteristics of apex carnivore communication and reproductive behaviors to predict responses to future human development - Veronica Yovovich; Maximilian L. Allen; Luke T. Macaulay; Christopher C. Wilmers (Biodiversity and Conservation, 2020)

Interactions between two naturalised invasive predators in Australia: are feral cats suppressed by dingoes? - Benjamin L. Allen; Lee R. Allen; Luke K.-P. Leung (Biological Invasions, 2015)

The short-term effects of a routine poisoning campaign on the movements and detectability of a social top-predator - Benjamin L. Allen; Richard M. Engeman; Luke K–P. Leung (Environmental Science and Pollution Research, 2014)

Shrimp culture in inland low salinity waters - Luke A. Roy; D. Allen Davis; I. Patrick Saoud; Chris A. Boyd; Harvey J. Pine; Claude E. Boyd (Reviews in Aquaculture, 2010)
Inland aquaculture of shrimp in low salinity waters is widespread in many regions worldwide. Owing to its ability to grow and survive in low salinity environments the Pacific white shrimp, ( Litopenaeus vannamei Boone) has become the candidate of choice for low salinity culture. Remediation techniques have been developed to improve the osmoregulatory capacity of shrimp reared in low salinity waters. These techniques have evaluated water modification strategies that improve low salinity waters used for production by adding potassium and magnesium fertilizers and dietary approaches that involve modification of the feeds offered to shrimp with supplements that might improve osmoregulatory capacity. Based on our own experience as well as what we found predominantly in the literature, it appears that modification of the rearing medium with potassium and magnesium fertilizers is more effective than dietary modification techniques at improving the growth, survival and osmoregulatory capacity of shrimp reared in low salinity waters.

Elevation of Transgene Expression Level by Flanking Matrix Attachment Regions (MAR) is Promoter Dependent: A Study of the Interactions of Six Promoters with the RB7 3′ MAR - S. Luke Mankin; George C. Allen; Thomas Phelan; Steven Spiker; William F. Thompson (Transgenic Research, 2003)

Introduction of a plant intron into the luciferase gene ofPhotinus pyralis - S. Luke Mankin; George C. Allen; William F. Thompson (Plant Molecular Biology Reporter, 1997)